EXAMINATION OF PUSAN CLAYS AT A REFERENCE TESTING SITE - S. G. Chung; p H. Giao (Lowland Technology International, 2001)
In early 2000, five special testing sites were proposed by Dong-A University's Brain Korea 21 Project, to look into some unusual geotechnical characteristic of Pusan clays. In this paper, the concept of a reference testing site and the way in which it has been set up and investigated are presented. Some of the results of both laboratory and in situ testing at a reference site are reported for illustration. The newly obtained data were analyzed and presented using both conventional and novel approaches in soft clay engineering. The initial results have demonstrated the benefits of having a reference testing site for moving toward a better characterization of Pusan clays. Such a practice can be considered as a useful step in geotechnical investigation of low land areas in the Nakdong river plain.